2001
DOI: 10.1002/1438-9312(200106)103:6<407::aid-ejlt407>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

N-3 to n-6 fatty acids for managing hyperlipidemia, diabetes, hypertension and atherosclerosis: Is there evidence?

Abstract: IntroductionThe aim of this review is to cover the role of fatty acids (FA) in atherosclerosis and related disorders from the perspective of a clinician. It will therefore be almost exclusively focussed on human data. It will also necessarily reflect the experience gained at an institution located in the Mediterranean area, which devoted more than 30 years of nutritional research in relation to cardiovascular disease under the guidance of Mario Mancini. The Mediterranean area remains a southern relative of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 117 publications
0
1
0
1
Order By: Relevance
“…A possible adverse effect of n-3 fatty acids on glucose homeostasis in diabetic patients had been suggested in earlier studies. Most of these used a high dose of fish oil resulting in an increased total energy and fat intake [76]. Other, well designed and placebo-controlled studies, with lower doses of fish oil showed no deleterious effect on glycaemic control [77][78][79].…”
Section: Polyunsaturated Fatty Acids (Pufa)mentioning
confidence: 99%
“…A possible adverse effect of n-3 fatty acids on glucose homeostasis in diabetic patients had been suggested in earlier studies. Most of these used a high dose of fish oil resulting in an increased total energy and fat intake [76]. Other, well designed and placebo-controlled studies, with lower doses of fish oil showed no deleterious effect on glycaemic control [77][78][79].…”
Section: Polyunsaturated Fatty Acids (Pufa)mentioning
confidence: 99%
“…Veoma obiman pregled istraţivanja uticaja masnih kiselina i antioksidanata (prvenstveno vitamina E) u ishrani ljudi na području Mediterana (populacija srednje generacije muškaraca) na povišenu količinu masnoše u krvi, dijabetesa, povišenog krvnog pritiska i arteroskleroze je potvrdio značaj ovih nutrijenata u preventivi i lečenju kardiovaskularnih bolesti (Rubba and Iannuzzi, 2001).…”
Section: Uloga Lipida I Esencijalnih Masnih Kiselina U Pravilnoj Ishraniunclassified